Could the Internet of Things Be Used to Enhance Student Nurses’ Experiences in a Disaster Simulation? - Laplante, Nancy L. (Online J Nurs Inform, 2018)
The Internet of Things (IoT) created opportunities for enhancing human lives. A recent undergraduate nursing disaster simulation experience prompted a thought as to whether IoT technologies could further enhance the educational experience of undergraduate nursing students in future disaster simulations.